2022
DOI: 10.7759/cureus.29944
|View full text |Cite|
|
Sign up to set email alerts
|

A Cross-Sectional Study of the Knowledge, Attitude, and Practice of Self-Medication Among the General Population in the Western Region of Saudi Arabia

Abstract: IntroductionSelf-medication (SM) is defined as consuming pharmaceutical drugs without the advice of a physician for either diagnosis or treatment. Reliance on self-medication has become a more common worldwide issue and now plays a major role in self-care. However, the practice is linked to many risks for patients and the whole community. This study assesses knowledge, attitudes, and practices associated with self-medication in the western region of Saudi Arabia. MethodsThis is an observational questionnaire-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…This study revealed that the most common conditions encouraging self-medication were pain, fever and cough. This is in contrast from another study in which common cold was found to be most common cause followed by fever and headache (22). This finding is in line with a study held in Rawalpindi where most of the students were taking medication for the relief of pain (23).…”
Section: Discussionsupporting
confidence: 83%
“…This study revealed that the most common conditions encouraging self-medication were pain, fever and cough. This is in contrast from another study in which common cold was found to be most common cause followed by fever and headache (22). This finding is in line with a study held in Rawalpindi where most of the students were taking medication for the relief of pain (23).…”
Section: Discussionsupporting
confidence: 83%
“…59 Compared to current research, only 26% of individuals engaged in self-medication practices, despite advancements in healthcare services, larger sample sizes, and improved methods of data collection employed in the studies above. Other studies conducted in Columbia and Saudi Arabia also showed a higher prevalence of selftreatment, 60,61 pointing to the necessity for addressing the factors that drive individuals to self-medicate of which the most common were fears related to infection, quarantine, and societal stigma were the predominant motivations for selfmedication. 62,63 However, studies done on self-medication during COVID-19 pandemic in: United States 13%, Australia 11%, Germany 11%, Spain 9%, United Kingdom 9%, Mexico 8%, and Italy 8% 64 showed disparity with the current report which may be due to drug policies and better health infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacists (72.6%) were the primary source of selfmedication information, followed by outdated prescriptions for prior illnesses (25.7%) and prescriptions from friends and family (1.8%) [27,29]. Table 1 depicts the common reasons, symptoms, sources, and drug groups used for self-medication [9,11,12,20,[23][24][25]30,31].…”
Section: Sources Of Self-medicationmentioning
confidence: 99%
“…The practice of self-medication is associated with several dangers for patients and the general public [30].…”
Section: Potential Risksmentioning
confidence: 99%